A randomized controlled trial on a minimally invasive microsurgical versus conventional procedure for the management of localized gingival recession in esthetic zone using alloderm - Robin Srivastava (Journal of Pharmacy and Bioallied Sciences, 2021)
Background: Microsurgical technique is a recent advancement in periodontal plastic surgery, which improves the predictability of periodontal procedures, providing better esthetic results with minimal postoperative discomfort. Alloderm is an alternate to connective tissue grafts, which has been successfully used for root coverage. The present study aims at Comparative assessment of Micro and Conventional surgical techniques for root coverage using coronally positioned flap (CPF) with Alloderm. Materials and Methods: Twenty sites with Miller's Class I or II gingival recession defects were selected; sites were randomly divided into control and test groups. Test sites were treated with CPF and acellular dermal matrix (ADM) using Microsurgery and control sites were treated with CPF and ADM using conventional method. Results: Conventional and Microsurgical procedures for root coverage showed a statistically significant difference in all clinical parameters from baseline to 3 and 6 months (P < 0.01). The microsurgical technique demonstrated a significant difference in ultrasonographic thickness of gingiva (P < 0.003) and patient satisfaction score (P < 0.005). Conclusion: Microsurgical procedure for root coverage was found to be superior to the conventional macrosurgical approach under magnification. Microsurgical sites healed faster with neovascularization demonstrated on ultrasonographic evaluation with improved gingival thickness and patient satisfaction scores.